Short-term compressive strength of fly ash and waste glass alkali-activated cement based binder (AACB) mortars with two biopolymers - Abdollahnejad, Zahra (2017)
The Roadmap to a Resource Efficient Europe aims that by 2020, waste will be managed as a resource. Thus materials that have the ability for the reuse of several types of wastes, such as alkali-activated cement-based binders (AACBs), will merit special attention. Some wastes like fly ash deserve special attention because they are generated in high amounts and have a very low reuse rate. This paper reports experimental results regarding the influence of the mix design of fly ash and waste glass AACB mortars containing two different biopolymers (carrageenan and xanthan) on their short-term mechanical performance. Microstructure and cost analysis are also included. The results show that a mixture of 80% fly ash, 10% waste glass, and 10% calcium hydroxide activated with an alkaline activator has the highest compressive strength. The results also show that the mortars with minor biopolymer carrageenan content are associated with a relevant increase in compressive strength and that the use of 0.1% of carrageenan leads to optimum compressive strength in most mixtures. The use of xanthan shows no beneficial effects on the compressive strength of AACB mortars. Several mixtures with xanthan even show a reduction in the compressive strength.